EDUCATIONAL REFORM AND STUDENTS’ SUBJECTIVITY PROSPECTS - Vladimir V. Molodin; Sergey G. Gorin (Высшее образование в России)
The article considers problems of students’ subjectivity development and change in the process of reforming the educational system. The authors note the fact of subjectivity redistribution between the educational process participants in the circumstances of strengthening student-centered approach in education, presupposing interactivity and breaking with the traditionalist intentions in positioning the student as only an object of education. Contemporaryeducational processis presented as an “agent-agent” interaction, when student not only experiences an informational influence, but also influences, though indirectly, reforming the education system from within.For the empirical basis the article uses the results of sociological surveys among students and teachers of the Novosibirsk State Academy of Architecture and Arts (NSAAA).